2014
DOI: 10.1007/s10517-014-2653-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Effect of Uridine and Uridine-5’-Monophosphate in Acute Myocardial Ischemia

Abstract: Experiments on rats with acute myocardial ischemia accompanied by early postocclusive arrhythmias have shown normalizing, energy-stabilizing, and antiarrhythmic effects of uridine and uridine-5'-monophosphate. The drugs decreased lactate and restored reserves of glycogen and creatine phosphate depleted by ischemia. Uridine and uridine-5'-monophosphate significantly decreased the severity of ventricular arrhythmias. Both drugs reduced the incidence and duration of fibrillation. Uridine -5'-monophosphate demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Some studies found that uridine had protective effects on cardiovascular diseases. Early studies by Krylova et al found that uridine and uridine-5′-monophosphate could reduce lactic acid, improve energy metabolism, and playe a protective role in myocardial ischemia and arrhythmias (including ventricular premature, ventricular tachycardia and ventricular fibrillation) ( 39 , 40 ). Recent studies found that uridine could prevent myocardial injury in ischemia and reperfusion rat models by activating mitochondrial pathway, prevented the decrease of cell energy supply and antioxidant system activity, thus improving energy supply ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that uridine had protective effects on cardiovascular diseases. Early studies by Krylova et al found that uridine and uridine-5′-monophosphate could reduce lactic acid, improve energy metabolism, and playe a protective role in myocardial ischemia and arrhythmias (including ventricular premature, ventricular tachycardia and ventricular fibrillation) ( 39 , 40 ). Recent studies found that uridine could prevent myocardial injury in ischemia and reperfusion rat models by activating mitochondrial pathway, prevented the decrease of cell energy supply and antioxidant system activity, thus improving energy supply ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uridine, a pyrimidine nucleoside, is more abundant in human plasma than other nucleosides 35 and is critical in the synthesis of endogenous pyrimidine, glycogen, biomembranes and the like 36 . Uridine modulates heart rhythm disorders through its participation in myocardial glycogen resynthesis and ATP production for ion transport systems under pathological conditions 37 . Fibrosis has been well established and exerts a crucial effect in the development of AF 38 .…”
Section: Discussionmentioning
confidence: 99%
“…We first performed DrugBank database searches and revealed ISG20 as a UMP target. UMP was demonstrated to possess an anti-fibrillatory effect by activating energy metabolism ( 32 ). Unfortunately, our experiments failed to find UMP-regulated ISG20 expression in cancer cells.…”
Section: Discussionmentioning
confidence: 99%